2006
DOI: 10.1007/s00436-006-0204-1
|View full text |Cite
|
Sign up to set email alerts
|

Expressed sequence tag analysis of adult Clonorchis sinensis, the Chinese liver fluke

Abstract: Expressed sequence tag (EST) pools represent partial profiles of the gene expressions of organisms. In an effort to construct a Clonorchis sinensis EST pool, 2,387 ESTs were collected from an adult C. sinensis cDNA library and assembled into 1,573 clusters. Of these clusters, 1,225 ESTs (51%) were singletons and 348 clusters consisted of more than two ESTs. There were 848 clusters (54%) that shared significant identity with previously reported proteins, and of these, 401 clusters were categorized into 11 major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…Total RNA was isolated by CsCl ultracentrifugation as described previously (Cho et al 2006), and first strand cDNA was synthesized from mRNA using oligo(dT) primer and reverse transcriptase (PowerScriptTM, Clontech, Palo Alto, CA). SMART VI (5′-AAG CAGTGGTAATCAACGCAGAGTGGGAATTCCGGC CGGG-3′) primer was then annealed to the deoxycytidine stretch synthesized at 3′ end of the first strand cDNA by terminal transferase activity of the reverse transcriptase.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was isolated by CsCl ultracentrifugation as described previously (Cho et al 2006), and first strand cDNA was synthesized from mRNA using oligo(dT) primer and reverse transcriptase (PowerScriptTM, Clontech, Palo Alto, CA). SMART VI (5′-AAG CAGTGGTAATCAACGCAGAGTGGGAATTCCGGC CGGG-3′) primer was then annealed to the deoxycytidine stretch synthesized at 3′ end of the first strand cDNA by terminal transferase activity of the reverse transcriptase.…”
Section: Methodsmentioning
confidence: 99%
“…[10][11][12] Cysteine proteases make up a large proportion of the total transcripts of each of trematode parasites studied to date. For example, nearly 15% of the transcripts derived from adult F. hepatica (http://www.sanger.ac.uk/Projects/Helminths/), 13 10% from adult C. sinensis, 14,15 as well as 18% and 27% from adult diploid and triploid P. westermani, respectively, 16 encode cysteine proteases. Cathepsin L, F and B proteases are often found DPRQJ WKH SUR¿OH RI PROHFXOHV VHFUHWHG E\ WUHPDWRGHV WHUPHG WKHLU VHFUHWRPH DOVR known as excretory-secretory proteins; ES), which allows them to perform a number of critical extracellular roles in parasite-host interactions.…”
Section: Trematode Cysteine Proteasesmentioning
confidence: 99%
“…Analyses of the expressed sequence tags (ESTs) of C. sinensis have revealed that proteases constitute a large proportion of the protein population of the flukes [8,9], which implies their physiological significance. The cysteine proteases of C. sinensis are developmentally regulated and are essential for fluke survival in terms of the contributions they make to biological processes, such as, stage transition, nutrient uptake, and immune evasion [64,65].…”
Section: Proteasesmentioning
confidence: 99%
“…A total of 3,221 ESTs of C. sinensis has been registered in public dbEST databases (http://www.ncbi.nlm.nih.gov/dbEST); 2,802 ESTs from the adults and 415 from the metacercariae [8,9,20]. In adult C. sinensis, the genes abundantly expressed in decreasing order were; groups of metabolic enzymes, regulatory and signal proteins, structure and cytoskeletal proteins, transcription and translation machinery proteins, and proteases and inhibitors.…”
Section: Expressed Sequence Tagsmentioning
confidence: 99%
See 1 more Smart Citation